Morphology, Distribution and Phenotype of Polycystin Kidney Disease 2-like 1-Positive Cerebrospinal Fluid Contacting Neurons in The Brainstem of Adult Mice - Orts-Del’Immagine, Adeline (Public Library of Science, 2014)
The mammalian spinal cord and medulla oblongata harbor unique neurons that remain in contact with the cerebrospinal fluid (CSF-cNs). These neurons were shown recently to express a polycystin member of the TRP channels family (PKD2L1) that potentially acts as a chemo- or mechanoreceptor. Recent studies carried out in young rodents indicate that spinal CSF-cNs express immature neuronal markers that appear to persist even in adult cells. Nevertheless, little is known about the phenotype and morphological properties of medullar CSF-cNs. Using immunohistochemistry and confocal microscopy techniques on tissues obtained from three-month old PKD2L1:EGFP transgenic mice, we analyzed the morphology, distribution, localization and phenotype of PKD2L1(+) CSF-cNs around the brainstem and cervical spinal cord central canal. We show that PKD2L1(+) CSF-cNs are GABAergic neurons with a subependymal localization, projecting a dendrite towards the central canal and an axon-like process running through the parenchyma. These neurons display a primary cilium on the soma and the dendritic process appears to bear ciliary-like structures in contact with the CSF. PKD2L1(+) CSF-cNs present a conserved morphology along the length of the medullospinal central canal with a change in their density, localization and dendritic length according to the rostro-caudal axis. At adult stages, PKD2L1(+) medullar CSF-cNs appear to remain in an intermediate state of maturation since they still exhibit characteristics of neuronal immaturity (DCX positive, neurofilament 160 kDa negative) along with the expression of a marker representative of neuronal maturation (NeuN). In addition, PKD2L1(+) CSF-cNs express Nkx6.1, a homeodomain protein that enables the differentiation of ventral progenitors into somatic motoneurons and interneurons. The present study provides valuable information on the cellular properties of this peculiar neuronal population that will be crucial for understanding the physiological role of CSF-cNs in mammals and their link with the stem cells contained in the region surrounding the medullospinal central canal.